Development of a Novel Biosensor-Driven Mutation and Selection System via in situ Growth of Corynebacterium crenatum for the Production of L-Arginine - Xu, Meijuan; Liu, Pingping; Chen, Jiamin; Peng, Anqi; Yang, Taowei; Zhang, Xian; Xu, Zhenghong; Rao, Zhiming (Frontiers in Bioengineering and Biotechnology, 2020)
The high yield mutants require a high-throughput screening method to obtain them quickly. Here, we developed an L-arginine biosensor (ARG-Select) to obtain increased L-arginine producers among a large number of mutant strains. This biosensor was constructed by ArgR protein and argC promoter, and could provide the strain with the output of bacterial growth via the reporter gene sacB; strains with high L-arginine production could survive in 10 % sucrose screening. To extend the screening limitation of 10 % sucrose, the sensitivity of ArgR protein to L-arginine was decreased. Corynebacterium crenatum SYPA5-5 and its systems pathway engineered strain Cc6 were chosen as the original strains. This biosensor was employed, and L-arginine hyperproducing mutants were screened. Finally, the HArg1 and DArg36 mutants of C. crenatum SYPA5-5 and Cc6 could produce 56.7 g L-1 and 95.5 g L-1 of L-arginine, respectively, which represent increases of 35.0 % and 13.5 %. These results demonstrate that the transcription factor (TF)-based biosensor could be applied in high yield strains selection as an effective high-throughput screening method.